Tuning Conjugated Polymer Chain Packing for Stretchable Semiconductors - Xu, Jie; Wu, Hung‐Chin; Mun, Jaewan; Ning, Rui; Wang, Weichen; Wang, Ging‐Ji Nathan; Nikzad, Shayla; Yan, Hongping; Gu, Xiaodan; Luo, Shaochuan; Zhou, Dongshan; Tok, Jeffrey B.‐H.; et al. (Advanced materials (Weinheim), 2022)
In order to apply polymer semiconductors to stretchable electronics, they need to be easily deformed under strain without being damaged. A small number of conjugated polymers, typically with semicrystalline packing structures, have been reported to exhibit mechanical stretchability. Herein, a method is reported to modify polymer semiconductor packing‐structure using a molecular additive, dioctyl phthalate (DOP), which is found to act as a molecular spacer, to be inserted between the amorphous chain networks and disrupt the crystalline packing. As a result, large‐crystal growth is suppressed while short‐range aggregations of conjugated polymers are promoted, which leads to an improved mechanical stretchability without affecting charge‐carrier transport. Due to the reduced conjugated polymer intermolecular interactions, strain‐induced chain alignment and crystallization are observed. By adding DOP to a well‐known conjugated polymer, poly[2,5‐bis(4‐decyltetradecyl)pyrrolo[3,4‐c]pyrrole‐1,4‐(2H,5H)‐dione‐(E)‐1,2‐di(2,2′‐bithiophen‐5‐yl)ethene] (DPPTVT), stretchable transistors are obtained with anisotropic charge‐carrier mobilities under strain, and stable current output under strain up to 100%. Bulky additive molecules residing between amorphous chain networks can disrupt the crystalline ordering of polymer semiconductors. The long‐range crystalline domains are suppressed while short‐range aggregations of conjugated polymers are promoted, leading to an improved thin‐film stretchability without affecting charge transport under an external strain up to 100%.